(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India joined the ranks of countries that have accepted the UN Convention on the Rights of theChild since 1992, yet the topic of child rights protection is seldom brought up in public discourse.Numerous laws in India provide a legal framework for discovering and punishing instances of child labor,including the Child Labour Act, of 1986 and the Juvenile Justice of Children Act, of 2000. No one under theage of fourteen should be employed in factories, mines, or other potentially hazardous jobs, and all minorsshould be subject to appropriate controls about their working situations. The Child Labor Act of 1986 wasenacted with this overarching purpose in mind. In the name of the Child’s Rights Convention lays out fourfundamental rights for children the right to survive, the right to grow, the right to participate, and theright to be protected. However, in India, children are still not seen as a distinct group demanding specialprotections. To further safeguard children’s rights in the workplace, further laws have been enacted. The2009 Integrated Child Protection Scheme, the 2010 Indira Gandhi Matritva Sahyog Yojana, the 2010 RajivGandhi Scheme for the Empowerment of Adolescent Girls, and 2012 The Integrated Child DevelopmentProgram have been reorganized. Despite all the laws that already exist, researchers stress theimportance of properly implementing the laws discussed in this article and note that the involvement ofall members of the family, the community, and the society at large is essential to safeguarding ourfuture, which means the healthy development of every child in the nation.